Thermal Comfort and Energy Performance of Atrium in Mediterranean Climate - Aram, Reihaneh; Alibaba, Halil Zafer (Mdpi, 2019)
This paper aims to determine the optimal single-story office building model with a corner atrium regarding different atrium orientations and office-building window-opening ratios in the Mediterranean climate via EDSL Tas software. When window-opening ratios were 25% and 50% at the northeast and southeast orientations of atriums and office spaces, thermal comfort was achieved according to categories B and C, respectively, within the cold season. Additionally, for the northeast atrium orientation with 25%, 137.2 W and 189.5 W of heat loss and gain in the office zone, and 37.7 W and 204.7 W of heat loss and gain in the atrium zone were recorded. Moreover, for the northeast atrium orientation with 50%, 134.5 W and 134.2 W of heat loss and gain in the office zone, and 40 W and 192 W of heat loss and gain in the atrium zone were recorded. On the other hand, for the southeast atrium orientation with 25%, 108.7 W and 143 W of heat loss and gain in the office zone, and 68.8 W and 130 W of heat loss and gain in the atrium zone were recorded, while, with 50%, 111.7 W and 142.7 W of heat loss and gain in the office zone, and 67.5 W and 121.2 W of heat loss and gain in the atrium zone were recorded. In the warm season, the atrium and office spaces were not thermally comfortable.
Keywords: thermal comfort; energy performance; atrium; EDSL Tas; predicted mean vote (PMV); predicted percentage of dissatisfied (PPD)